Ansible for Real-Life Automation A Complete Ansible Handbook Filled with Practical IT Automation Use Cases - Madapparambath, Gineesh (Packt Publishing, Limited, 2022)
Get ready to leverage the power of Ansible's wide applicability to automate and manage IT infrastructure with Ansible for Real-Life Automation. This book will guide you in setting up and managing the free and open source automation tool and remote-managed nodes in the production and dev/staging environments. Starting with its installation and deployment, you'll learn automation using simple use cases in your workplace. You'll go beyond just Linux machines to use Ansible to automate Microsoft Windows machines, network devices, and private and public cloud platforms such as VMWare, AWS, and GCP. As you progress through the chapters, you'll integrate Ansible into your DevOps workflow and deal with application container management and container platforms such as Kubernetes. This Ansible book also contains a detailed introduction to Red Hat Ansible Automation Platform to help you get up to speed with Red Hat AAP and integration with CI/CD and ITSM. What's more, you'll implement efficient automation solutions while learning best practices and methods to secure sensitive data using Ansible Vault and alternatives to automate non-supported platforms and operations using raw commands, command modules, and REST API calls. By the end of this book, you'll be proficient in identifying and developing real-life automation use cases using Ansible.